Montgomery Identity and Ostrowski Type Inequalities for Riemann-Liouville Fractional Integral - Andrea Aglić Aljinović (Journal of Mathematics)
We present Montgomery identity for Riemann-Liouville fractional integral as well as for fractional integral of a function f with respect to another function g. We further use them to obtain Ostrowski type inequalities involving functions whose first derivatives belong to Lp spaces. These inequalities are generally sharp in case p>1 and the best possible in case p=1. Application for Hadamard fractional integrals is given.